In-Vitro Hepatoprotective Activities of Pergularia daemia and Terminalia catappa L leaf extracts - Packiriswamy, Vijaya; Parameswaran, Indumathi; Krishnamurthi, Vijayalakshmi (Journal of Neonatal Surgery, 2025)
Plant based products are currently used for different alignments with less side effects than the chemical derived drugs. Plants are rich in secondary phytochemicals like polyphenols, flavonoids, terpenoids and tannins with lot of pharmacological activities. In this work the hydroethanolic leaf extracts of Pergularia daemia and Terminalia catappa was subjected to silica gel chromatography and gradually eluted with Hexane, Ethyl acetate, Ethanol, Methanol, Water. The column fractions were collected form each plant extracts. The above fractions were used to study the hepatoprotective activities in cell line studies. From MTT assay the Maximum cell viability was observed in two column fractions of Pergularia daemia and Terminalia catappa. These fractions are used to study the invitro hepatoprotective activity in different concentrations. The selected fractions were used to assessed the hepatoprotective in hepatocytes cell lines. Hepatoprotectivity was observed by cell viability and SGOT and SGPT in different concentration of extracts.